Is prolactin receptor signaling a target in dopamine-resistant prolactinomas? - Ferraris, Jimena (Frontiers in Endocrinology, 2023)
The hypothalamic neuroendocrine catecholamine dopamine regulates the lactotroph function, including prolactin (PRL) secretion, proliferation, and apoptosis. The treatment of PRL-secreting tumors, formerly known as prolactinomas, has relied mainly on this physiological characteristic, making dopamine agonists the first therapeutic alternative. Nevertheless, the group of patients that do not respond to this treatment has few therapeutical options. Prolactin is another physiological regulator of lactotroph function, acting as an autocrine/paracrine factor that controls PRL secretion and cellular turnover, inducing apoptosis and decreasing proliferation. Furthermore, the signaling pathways related to these effects, mainly JAK/STAT and PI3K/Akt, and MAPK, have been extensively studied in prolactinomas and other tumors as therapeutic targets. In the present work, the relationship between prolactinoma pathophysiology and PRL development is explored, aiming to comprehend the value of PRL and PRLR-associated pathways as exploratory fields alternative to dopamine-related approaches, which are worth physiological characteristics that might be impaired and can be potentially restored or upregulated to provide more options to the patients.